Variation in Antithrombotic Therapy and Clinical Outcomes in Patients With Preexisting Atrial Fibrillation Undergoing Transcatheter Aortic Valve Replacement: Insights From the Society of Thoracic Surgeons/American College of Cardiology Transcatheter Valve Therapy Registry. (April 2021) - Sherwood, Matthew W.; Gupta, Aakriti; Vemulapalli, Sreekanth; Li, Zhuokai; Piccini, Jonathan; Harrison, J. Kevin; Dai, David; Vora, Amit N.; Mack, Michael J.; Holmes, David R.; Rumsfeld, John S.; Cohen, David J.; et al.
Abstract : Background: Optimal antithrombotic management of patients with preexisting atrial fibrillation undergoing transcatheter aortic valve replacement is challenging given the need to balance the risk of bleeding and thromboembolism. We aimed to examine variation in care and association of antithrombotic therapies with 1-year outcomes of stroke, bleeding, and mortality in patients undergoing transcatheter aortic valve replacement with concomitant atrial fibrillation in the United States. Methods: Patients who underwent transcatheter aortic valve replacement with preexisting atrial fibrillation from November 2011 through September 2015 in the Society of Thoracic Surgeons/American College of Cardiology Transcatheter Valve Therapy registry linked to the Medicare database were examined according to receipt of oral anticoagulants (OACs) or antiplatelet therapies (APTs) or a combination of these (OAC+APT) at discharge. To assess the associations of antithrombotic therapies with 1-year outcomes of stroke, bleeding, and mortality, we utilized inverse probability weighting for antithrombotic therapies and multivariable regression modeling to adjust for patient- and hospital-level variables. Results: In the 11 382 patients included in our study, 5833 (51.2%) were discharged on OAC+APT, 4786 (42.0%) on APT alone, and 763 (6.7%) on OAC alone. There was significant variability in discharge medication patterns, including 42% of patients discharged without OAC therapy. In adjusted analyses, the risk for all-cause mortality and stroke was not significantly different when comparing the 3 different antithrombotic strategies. Risk of bleeding was higher with OAC+APT compared with APT alone (hazard ratio, 1.16 [95% CI, 1.05–1.27]) and similar compared with OAC alone (hazard ratio, 1.17 [95% CI, 0.93–1.47]). Conclusions: There was significant variability in discharge medication patterns across US sites in patients with atrial fibrillation undergoing transcatheter aortic valve replacement, including significant underuse of OAC in this high-risk cohort. The use of OAC+APT (versus OAC alone or APT alone) was not associated with a lower risk of stroke or mortality but was associated with increased risk of bleeding complications at 1 year compared with APT alone.